Determination of soil pollution derived from polychlorinated biphenyls (PCBs) in Bursa: spatial and temporal variations - Büşra Tandoğan; Gizem Eker Sanlı (MANAS: Journal of Engineering)
The soil is anatural reservoir and a transporter component of the terrestrial ecosystem forpolychlorinated biphenyls (PCBs). The determination of PCBs is important to identify the necessary precautious steps to betaken.The objective of this study is to determine seasonal and regional PCBvariations in the soil in Bursa-Turkey. In this context, soil samples werecollected from 19 different points during summer and winter seasons andanalyzed by gas chromatography-electron capture detector (GC-ECD) for S82 PCB. Theregional variation of S82 PCBconcentrations was 0.03-85 ng/g dry matter (DM). The highest S82 PCBconcentration was measured sampling points near the iron-steel plant in bothseasons. At all sampling points, S82 PCBconcentrations were higher in winter than those in summer. In general,high-chlorinated homologes groups (>6-CBs) in summer and low-chlorinatedhomologes groups (<5-CBs) dominated in winter. Also, a significantcorrelation was found between the heavy species (>5-CBs) and TOC, while nosignificant correlation was observed between the light species (<5-CBs) andTOC. The S7 PCB range of winter and summerseasons is 0.043-3.87 ng/g DM and 0.02-1.97 ng/g DM, respectively. The averageDutch S7 PCB concentration in winter was0.735 ± 1.05 ng/g DM, while in summer it was 0.462 ± 0.72 ng/g DM.